Laboratory Diagnosis, Safety and Testing Strategies of Novel SARS COV 2 - Baliga, Shrikala; Shenoy, Suchitra; Rao, Pooja (Indian Journal of Community Health, 2020)
The COVID 19 Pandemic is the most defining health care crisis of the present times. It has challenged the health care facilities, overwhelmed the health care personnel and baffled the scientists and researchers. There is no quick fix in a pandemic of this proportion. The past four months has seen many new aspects of this disease, and newer evolving strategies to rein in the pandemic. This commentary seeks to deal with the various aspects of laboratory diagnosis, safety and testing strategies adopted by different countries.